Recycling plastics into interior home accessories - Badrina, Lilianne L.
This thesis generally aimed to focus on encouraging recycling projects among Filipino families. Specifically, it aimed to tackle the feasibility of interior home accessories from salvaged materials. This study was a response to the arising interest and need of Filipinos for a resource material on what can be done to minimize home expenditures, especially with the prevalent economic crisis. At the same time, this study was for pollution-control purposes. The research method was used in gathering the data. All available data were exhausted and used in form of observation, documentation and providing solution to support the project. This study was able to find out that the Philippines still has along way to improve on its technology in order to increase productivity and profit earnings; thus, alleviating the buying power of its people on home comfort and luxuries. Meanwhile, our country is at a "salvaging" stage due to the arising economic crisis, aside from the existing problem of controlling pollution. The recycling of materials from almost any spent products had to be given considerable thought. Government must encourage more of its people to join such projects. It could create more jobs for the Filipinos: thus, increasing the country's product outputs.